User Experience Analysis on Mobile Application Design Using User Experience Questionnaire - Igor Didier Sabukunze; Alexis Arakaza (Indonesian Journal of Information Systems, 2021)
Nowadays, it is essential to use all concepts of Human-Computer interaction to understand mobile application design usability. This manuscript aimed to analyze a mobile application user experience (Grab online transportation), especially Grab foodservice users, using a user experience questionnaire since we noticed some Grab food users' complaints.  Researchers collected data from 90 respondents within six were not used because the excel data analysis tool found that there were suspicious. We finally analyzed using an excel data analysis tool. The findings have shown that all six scales of the User Experience Questionnaire (UEQ) are good except the dependability scale. In addition, the mean scale value computed is favorable, and all values are more significant than 0.8 compared to the UEQ benchmark. The findings can be used for dependability improvement to reduce complaints from users.